“Pengadilan Warganet” Terhadap Maladministrasi Pelayanan Publik - Mukromin, Ngutsman; Mujib, Mujib; Jumadi, Jumadi (Public Administration, Faculty of Politics and Social Science, Universitas Jenderal Soedirman, Indonesia, 2023)
The research entitled